The Influence of Service Quality towards Pegadaian Syariah Customer Satisfaction - Hasanah, Mifta (2010)
In the present economic situation, any economic institutions, either it is individual or government owned, will need huge amount of fund to begin any transaction. The need of funding will increase along with the growth of the institution, and every economic person will have to be able to overcome the need of funding throughout way of savings and loan. The activity can be held by an individual or corporation, one of them is The Pawning Institution. As a country with majority Muslim citizen, a pawning institution with Islamic principles also needed, and thus The Syariah Pawning Institution was established. This research explains the Syariah pawning in Indonesia, more precisely the quality of services which influences customer satisfaction by utilizing the service quality dimensions as indicator i.e. compliance, assurance, tangibility, reliability, empathy and responsiveness. These dimensions will determine the level of customer satisfaction within The Syariah Pawning Institution. Due to the fact that the presence of Syariah Pawning Institutions in Indonesia is still new, this research is expected to provide analysis and discussion so that the institutions will be able to enhance its performance and become better institution overtime. This research uses quantitative methods. The result of the research also shows that demographic factor can determine the level of customer satisfaction in Syariah pawnshops. Therefore it is expected that the result will be useful for The Syariah Pawning Institution, making it a better institutions and can be use as input in the upcoming research on Pawning and Syariah Pawning.